Análisis cinético de la pirólisis de biomasa (2018)
The coffee husk is a by-product of the coffee industry that is generated in proportion to the coffee grain production, which encourages the search for its energy use. This work is focused on the study of the reaction kinetics of the coffee husk pyrolysis process, where the kinetic parameters (activation energy and pre-exponential factor) were determined from a thermogravimetric analysis (TGA). A methodology was proposed that integrates isoconversion methods and fitting methods, in order to reduce the uncertainty generated by each one of them separately. As a result, a mechanism of 4 reactions was obtained, corresponding to the decomposition of the lignocellulosic compounds characteristic of biomass. For each of these reactions, the kinetic parameters were determined using the aforementioned methodology. The results obtained show broad agreement with what is reported in the literature.